The Corona Conundrum: A Shadow Pandemic of Mental Health Concerns - Khan, Romesa Qaiser; Farooq, Zara; Khan, Abdul Moiz (Annals of King Edward Medical University, 2020)
The COVID-19 pandemic and the resultant quarantine and lockdowns have led to a shadow pandemic of mental health disorders, economic instability, racial bias, surge of domestic abuse and spread of misinformation. While the focus has been on the mental health of frontline essential workers in this pandemic, its effects on the mental health of the vulnerable population such as known psychiatric patients, racial minorities, children and elderly have largely been ignored. If we are to prevent a post-pandemic mental health crises focus needs to be shifted to both include the vulnerable population in the research and to take urgent measures such as provision of online counselling, penalization of spread of misinformation and monitoring hate crime.